2020
DOI: 10.1039/d0cc01132k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced intersystem crossing in DNA oxidative lesions and epigenetic intermediates

Abstract: The propensity of 5-formyluracil and 5-formylcytosine, i.e. oxidative lesions and epigenetic intermediates, in acting as intrinsic DNA photosensitizers is unraveled by using a combination of molecular modeling, simulation and spectroscopy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…The latter is a gateway state to a triplet state formed with an approximately 70 % quantum yield. [6][7] Effective triplet-triplet energy transfer [8] has also been documented for 5fdCyd. Therefore, 5fdCyd has the potential to be an internal triplet photosensitizer which can initiate DNA photolesions.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The latter is a gateway state to a triplet state formed with an approximately 70 % quantum yield. [6][7] Effective triplet-triplet energy transfer [8] has also been documented for 5fdCyd. Therefore, 5fdCyd has the potential to be an internal triplet photosensitizer which can initiate DNA photolesions.…”
Section: Introductionmentioning
confidence: 91%
“…Prior transient absorption experiments on 5fdCyd revealed that the bright 1 ππ* state decays to a dark 1 nπ* state (located on the formyl group) on an ultrafast time scale in acetonitrile (ACN). The latter is a gateway state to a triplet state formed with an approximately 70 % quantum yield [6–7] . Effective triplet‐triplet energy transfer [8] has also been documented for 5fdCyd.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…30 Recently, the role of oxidative lesions, namely 5-formyluracil (ForU) 31 and 5-formylcytosine (ForC) 32,33 (see Scheme 1), as potential Trojan Horses has been studied through experiments 34 and theoretical calculations. [35][36][37] It has indeed been recognized, both in model systems and in DNA oligomers, that the inclusion of ForU is correlated with a significant increase in the yield of CPD damages. 34 Furthermore, molecular modeling and simulations have shown that ForU is prone to a facile ISC, leading to an energetically favorable TTET to thymine and that those conditions are maintained in the B-DNA environment.…”
Section: Introductionmentioning
confidence: 99%
“…35 Subsequently, it was shown that ISC is also possible in the case of ForC, even if non-adiabatic molecular dynamics have pointed out a less-favorable phenomenon as compared to ForU. 37 The behavior of ForC in comparison with ForU is indeed extremely intriguing, not only from a photophysical perspective, but also due to its biological relevance. ForC can be considered an oxidative lesion, but also an epigenetic intermediate in the demethylation process of 5-methyl-cytosine (5MetC).…”
Section: Introductionmentioning
confidence: 99%